Corporate Social Responsibility and Corporate Governance:A Bibliometric Review - Nor Rahma Rizka; Diana Putri (LP3M Universitas Putra Bangsa, 2025)
This study aims to map the development of literature or research related to corporate social responsibility (CSR) and corporate governance (CG) through a bibliometric approach. Data were obtained from the Scopus database and filtered based on the type of scientific document and only included articles in English, resulting in 1,530 for analysis. Bibliometric analysis includes annual publication trends, identification of authors and articles with the highest citations, and visualization of both topic networks, research time trends for related topics, and mapping of topic frequency levels to be raised in research. The results show a significant increase in publications from 2015 to 2024, with Krüger's (2015) article being the most cited. VOSviewer visualization reveals a strong relationship between CSR and CG with themes such as performance, firm value, and sustainability. This study not only maps the direction of scientific discourse development but also provides a strong foundation for further research that is more relevant to the needs of the era.